Diagnóstico del proceso de comercialización de calzado de la Empresa Dikalzaflex de la ciudad de Ambato - Navarrete Carvajal, Miguel Angel (2024)
The main objective of this thesis work is to carry out a diagnosis of the marketing process of the Dikalzaflex company, located in the city of Ambato. Through a detailed analysis of the different stages of the commercial process, theaim is to identify the strengths and weaknesses of the company, as well as the opportunities and threats present in the market environment. To carry out this study, qualitative and quantitative methods were used, including interviews and documentary analysis. The data collection allowed us toobtain a comprehensive view of current marketing procedures, covering aspects such as sales management, marketing strategies, distribution channels and customer satisfaction............